PERAN PEMBELAJARAN BUDAYA LOKAL DALAM PEMBENTUKAN KARAKTER SISWA MADRASAH IBTIDAIYAH (MI) - Bisarul Ihsan (Universitas Islam Darul 'Ulum Lamongan, 2019)
Abstract The purpose of the discussion of this article is in the background of the various conflicts that arise at this time, which relate to the level of morality of the people, both between classes and between officials, even children. With these considerations, the steps can be taken by strengthening the understanding of character through local literature and culture that can be collaborated into learning with material about human learning and the environment. This is very good to implement and starts with students who are still in elementary school / madrasah.